Community health nursing research priorities: a Delphi investigation - Downie, Jill; Henderson, Saraswathy; Juliff, D.; Munns, Ailsa; Wichmann, Helen (Cambridge Publishing, 2006)
The current paradigm of community health nursing presumes the integration of individual, family, group and community care, under a primary health care framework utilising the best available research evidence. However, the extent to which community health nurses (CHNs) meet this challenge is absent from the nursing literature. Existing research suggests nurses experience tension between the need to focus on broad primary health and health promotion issues whilst simultaneously being immersed in individual client concerns. Moreover, there is a dearth of literature to confirm research priorities for community health nursing that inform best practice initiatives. The aim of the study was to investigate the research priorities of community nurses in a health service region in metropolitan Perth, Western Australia.A descriptive study, utilising a two-round Delphi approach, was conducted with a population of 133 CHNs. Of the target population, 43% (n = 57) and 50% (n = 66) of nurses contributed their informed opinion across two Delphi rounds, respectively. In round two, nurses ranked eight health research categories according to 'importance to their area of work'. Elderly issues were ranked as the most important category over health service reorientation, partnership, youth health, Aboriginal health, lifestyle issues, mental health and family health. Nurses also rated 47 topics, which clustered under the eight health categories, in terms of their research priority for community health. Results demonstrated consensus (80%) for five major research priorities under the categories of mental health, youth health, and family health. The differences noted between the overall ranking of health research categories, and the categories to which the priority research topics belonged confirms the highly diversified nature of issues faced in routine community health practice. The findings support the continued relevance of issues identified under recent national health strategies. However, the topics rated as priority research areas in round two suggests gaps in primary research, educational preparedness or guidelines to integrate existing research into community health practice.